1995
DOI: 10.1021/jm00011a016
|View full text |Cite
|
Sign up to set email alerts
|

Cardioselective Antiischemic ATP-Sensitive Potassium Channel Openers. 2. Structure-Activity Studies on Benzopyranylcyanoguanidines; Modification of the Benzopyran Ring

Abstract: The ATP-sensitive potassium channel (KATP) openers are of considerable interest as myocardial protecting agents. However, there exists a narrow window of safety for the use of first-generation compounds as antiischemic agents due to their powerful peripheral vasodilating effects, which can result in underperfusion of the area already at risk. We have recently disclosed the discovery of benzopyranylcyanoguanidine type KATP openers (BMS-180448) which are more selective for the ischemic myocardium compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 10 publications
2
50
0
Order By: Relevance
“…It is speculated that the two methoxymethyl groups play an important role in coronary selective action [13]. Atwal et al [28] also reported a series of compounds with a benzopyran ring that have cardioselective actions. The benzopyranylcyanoguanidine type K ATP channel opener has antiischemic efficacy in animal models of myocardial ischemia without an effect on peripheral hemodynamic variables.…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that the two methoxymethyl groups play an important role in coronary selective action [13]. Atwal et al [28] also reported a series of compounds with a benzopyran ring that have cardioselective actions. The benzopyranylcyanoguanidine type K ATP channel opener has antiischemic efficacy in animal models of myocardial ischemia without an effect on peripheral hemodynamic variables.…”
Section: Discussionmentioning
confidence: 99%
“…(3)) was the first cardioselective KCO [42]. Starting from BMS-180448 Atwal et al [43][44][45][46][47] performed detailed SAR studies (Fig. 4).…”
Section: Cardioselective Benzopyranyl Cyanoguanidinesmentioning
confidence: 99%
“…4). Among benzopyran ring modifications [43], an exchange of the oxygen in 1-position by CH 2 is tolerated; exchange by NH is detrimental. The geminal 2-methyl groups are essential.…”
Section: Cardioselective Benzopyranyl Cyanoguanidinesmentioning
confidence: 99%
“…These compounds can be used in many industrial applications such as light sensitive sunglasses [3,4], molecular electronics [5], optical memories [6][7][8][9]. On the other hand, many natural naphtho-and benzopyrans exhibit pharmacological applications [10,11] such as anti-HIV [12], antihypertensive [13] and anti-ischaemic [14] properties.…”
Section: Introductionmentioning
confidence: 99%